IDNStudy.com, kung saan ang iyong mga tanong ay natutugunan ng mabilis na sagot. Tuklasin ang malawak na hanay ng mga paksa at makahanap ng maaasahang sagot mula sa mga bihasang miyembro ng aming komunidad.

Write the following in their general form and identify the vertex of the graph

1. f(x)=(x+3) ²+6
2. f(x) = -2(x+5)²+9
3. f(x)=-(x-7) ²- 2​


Sagot :

✒️ QUADRATIC FUNC.

[tex]••••••••••••••••••••••••••••••••••••••••••••••••••[/tex]

[tex] \large\underline{\mathbb{DIRECTIONS}:} [/tex]

» Write the following in their general form and identify the vertex of the graph.

  • 1. f(x) = (x+3)² + 6
  • 2. f(x) = -2(x+5)² + 9
  • 3. f(x)= -(x-7)² - 2

[tex]••••••••••••••••••••••••••••••••••••••••••••••••••[/tex]

[tex] \large\underline{\mathbb{ANSWER}:} [/tex]

General Form:

[tex] \qquad \large \: \rm 1) \; f(x) = x^2 + 6x + 15 [/tex]

[tex] \qquad \large \: \rm 2) \; f(x) = \text-2x^2 - 20x - 41 [/tex]

[tex] \qquad \large \: \rm 3) \; f(x) = \text-x^2 + 14x - 51 [/tex]

Vertices:

[tex] \qquad \large \: \rm 1) \; (\text-3,6) [/tex]

[tex] \qquad \large \: \rm 2) \; (\text-5,9) [/tex]

[tex] \qquad \large \: \rm 3) \; (7,\text-2) [/tex]

[tex]••••••••••••••••••••••••••••••••••••••••••••••••••[/tex]

[tex] \large\underline{\mathbb{SOLUTION}:} [/tex]

» Since the quadratic function is already in vertex form, we can find its vertex as (h, k).

  • [tex] f(x) = a(x - h)^2 + k [/tex]

» After taking the values of h and k, we can now rearrange the function in general form.

  • [tex] f(x) = ax^2 + bx + c [/tex]

[tex]•••\:•••\:•••\:•••\:•••\:•••\:•••\:•••\:•••\:•••\:•••\:•••\:•••[/tex]

Number 1:

» Since h is -3 and k is 6, then the vertex of the parabola is at (-3, 6). Now rearrange it in general form.

  • [tex] f(x) = (x + 3)^2 + 6 [/tex]

  • [tex] f(x) = x^2 + 6x + 9 + 6 [/tex]

  • [tex] f(x) = x^2 + 6x + 15 [/tex]

[tex] \therefore [/tex] f(x) = + 6x + 15 is the general form of the given quadratic function.

[tex]•••\:•••\:•••\:•••\:•••\:•••\:•••\:•••\:•••\:•••\:•••\:•••\:•••[/tex]

Number 2:

» Since h is -5 and k is 9, then the vertex of the parabola is at (-5, 9). Now rearrange it in general form.

  • [tex] f(x) = \text-2(x + 5)^2 + 9 [/tex]

  • [tex] f(x) = \text-2(x^2 + 10x + 25) + 9 [/tex]

  • [tex] f(x) = \text-2x^2 - 20x - 50 + 9 [/tex]

  • [tex] f(x) = \text-2x^2 - 20x - 41 [/tex]

[tex] \therefore [/tex] f(x) = -2- 20x - 41 is the general form of the given quadratic function.

[tex]•••\:•••\:•••\:•••\:•••\:•••\:•••\:•••\:•••\:•••\:•••\:•••\:•••[/tex]

Number 3:

» Since h is 7 and k is -2, then the vertex of the parabola is at (7, -2). Now rearrange it in general form.

  • [tex] f(x) = \text-(x - 7)^2 - 2 [/tex]

  • [tex] f(x) = \text-(x^2 - 14x + 49) - 2 [/tex]

  • [tex] f(x) = \text-x^2 + 14x - 49 - 2 [/tex]

  • [tex] f(x) = \text-x^2 + 14x - 51 [/tex]

[tex] \therefore [/tex] f(x) = -x² + 14x - 51 is the general form of the given quadratic function.

[tex]••••••••••••••••••••••••••••••••••••••••••••••••••[/tex]

(ノ^_^)ノ